Sistem Informasi Manajemen Budidaya Tanaman Melon Modul Pengelolaan Keuangan di CV Agro Utama Mandiri Lestari - Fitrah Maharani Humaira; Valentia Nikma Prastita; Tita Karlita; Rengga Asmara (Riau Jurnal Teknik Informatika, 2025)
The advancement of technology is progressing rapidly and will continue in line with the development of science. This progress is inevitable in all aspects of life, including in the corporate environment. CV Agro Utama Mandiri Lestari is a company engaged in agriculture as well as a training and self-sufficient rural development center. A company can grow quickly if its financial management data is accurate and precise. Financial management involves organizing the resources owned by the company to achieve its goals and objectives. In financial management, there are cash inflows and outflows, which are activities that always exist in every business entity. In this company, melon cultivation is still managed using a manual and simple financial system, making administrative activities prone to document loss, inaccuracy, and difficulties in analyzing fertilizer expenses. Therefore, a financial management system is highly necessary for CV Agro Utama Mandiri Lestari. This system features data management for income, expenses, human resources, harvests, capital, and profit and loss per harvest. Additionally, it can generate financial reports based on predefined filters. The system also provides a data visualization dashboard displaying financial information for CV Agro Utama Mandiri Lestari.